Inspired by Gandhi : Mahatma Gandhi's influence on significant leaders of nonviolence - Aklan, Anna Katalin (Array, 2020)
The leader of the Indian independence movement, Mahatma Gandhi, left an invaluable legacy: he proved to the world that it was possible to achieve political aims without the use of violence. He was the first political activist to develop strategies of nonviolent mass resistance based on a solid philosophical and uniquely religious foundation. Since Gandhi’s death in 1948, in many parts of the world, this legacy has been received and continued by others facing oppression, inequality, or a lack of human rights. This article is a tribute to five of the most faithful followers of Gandhi who have acknowledged his inspiration for their political activities and in choosing nonviolence as a political method and way of life: Khan Abdul Ghaffar Khan, Martin Luther King, Louis Massignon, the Dalai Lama, and Malala Yousafzai. This article describes their formative leadership and their significance and impact on regional and global politics and history.